Benefits of using sea sand and seawater in concrete: a comprehensive review. Issue 4 (2nd October 2019) - Dhondy, Tanaz; Remennikov, Alex; Shiekh, M. Neaz
ABSTRACT: The population worldwide is growing and so is the demand for more infrastructure. The rate of consumption of concrete has grown significantly over the years, becoming one of the most fundamental construction materials. This growth has depleted natural river sand and freshwater sources. The use of sea sand and seawater in concrete can provide sustainability to natural resources, while improving the mechanical properties of concrete. The corrosion of steel-reinforcement is inevitable with the use of sea sand seawater concrete. Therefore, non-corrosive Fibre-Reinforced-Polymers (FRP) is a solution. Reasons to consider the use of sea sand and seawater in concrete is to maintain natural resources, allowing construction to occur in an efficient and sustainable manner, eliminating the costs associated with the repairs of concrete spalling and to mitigate the adverse effects climate change has on existing steel-reinforced concrete structures.